Design of simulation tools hybrid transmission mechanism. Issue 1 (December 2020) - Kurnia, William; Halim, Agus; Purna Irawan, Agustinus
Abstract: Simulation tool is a learning facility that presents learning experiences using artificial situations or system models so that one can understand certain concepts. This design aims to create a simulation tool as a learning media for planetary gear mechanisms in hybrid transmission systems. The method used in the design uses the reverse engineering method which is focused on the mechanism of the planetary gear, so that it can be made into a simulation tool. The planetary gear component design are based on data from Toyota Prius reference system using a torque ratio, with planning power of 15 kW and a rotation of 300 r/min. The planetary gear system consists of a sun gear with a diameter of 75 mm and 25 pieces of teeth, a planetary gear with a diameter of 54 mm and 17 pieces of teeth, and a ring gear with a diameter of 18 mm and 60 pieces of teeth. The result of design shows that the hybrid transmission simulation tool mechanism can function well as a learning medium with variations of 3 outputs.